2012
DOI: 10.1186/1471-2393-12-63
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil patient controlled analgesia versus epidural analgesia in labour. A multicentre randomized controlled trial

Abstract: BackgroundPain relief during labour is a topic of major interest in the Netherlands. Epidural analgesia is considered to be the most effective method of pain relief and recommended as first choice. However its uptake by pregnant women is limited compared to other western countries, partly as a result of non-availability due to logistic problems. Remifentanil, a synthetic opioid, is very suitable for patient controlled analgesia. Recent studies show that epidural analgesia is superior to remifentanil patient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
1
27
0
4
Order By: Relevance
“…R-PCA reduced the incidence of pruritus when compared with EA, (OR 0.54; 95% CI, 0.32-0.89). Among the 5 studies that reported pruritus, Douma et al [8] used sufentanil, Freeman et al [14] used fentanyl or sufentanil, while the remainder [9][10]12,15] used fentanyl as an epidural opioid. Although the mechanism of neuraxial opioid-induced pruritus remains unclear, it is has been suggested that there may be activation of an itch center in the central nervous system and the medullary dorsal horn, potentially combined with antagonism of inhibitor itch transmitters [24].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…R-PCA reduced the incidence of pruritus when compared with EA, (OR 0.54; 95% CI, 0.32-0.89). Among the 5 studies that reported pruritus, Douma et al [8] used sufentanil, Freeman et al [14] used fentanyl or sufentanil, while the remainder [9][10]12,15] used fentanyl as an epidural opioid. Although the mechanism of neuraxial opioid-induced pruritus remains unclear, it is has been suggested that there may be activation of an itch center in the central nervous system and the medullary dorsal horn, potentially combined with antagonism of inhibitor itch transmitters [24].…”
Section: Discussionmentioning
confidence: 98%
“…Maternal satisfaction with labor analgesia was reported in all 6 studies [8][9][10][11][12][13][14][15]. However, the definition and methods of reporting satisfaction differed across the studies ( Table 2).…”
Section: Primary End Pointmentioning
confidence: 95%
See 1 more Smart Citation
“…Debido a sus potenciales efectos adversos, es necesario informar a la paciente 103 , monitorizarla adecuadamente 104,105 y formar al personal de enfermerĂ­a y matronas en su empleo. En Holanda, donde la analgesia epidural no estĂĄ completamente extendida a toda la poblaciĂłn, se ha llegado a recomendar la PCA de remifentanilo desde un punto de vista coste-efectividad como una tĂ©cnica analgĂ©sica de primera elecciĂłn 106 , aspecto que ha sido altamente criticado 107 . Los agonistas antagonistas (nalbufina, butorfanol, pentazocina y buprenorfina) tambiĂ©n se han usado, siendo su principal ventaja el efecto techo respecto a las dosis que causan depresiĂłn respiratoria (ej.…”
Section: Opioidesunclassified
“…Remifentanil is used in 1/3 of all of the obstetric hospitals in Holland [37], in which guidelines of management and delivery analgesia protocols have been devised [38]. In Italy, a study was conducted with a group of 205 parturients receiving RMFNT, and no newborn required naloxone [39].…”
mentioning
confidence: 99%